Sierra Leone : Poverty Reduction Strategy Paper-Progress Report; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Joint Staff Advisory Note describes the progress made on the Poverty Reduction Strategy Paper (PRSP) in Sierra Leone on the basis of the June 2008 progress report. The report analyzes key elements of the Poverty Reduction Strategy (PRS), including: macroeconomic performance; good governance, peace, and security; pro-poor sustainable growth for food security and job creation; human resource development; and monitoring and evaluation of the PRS. The progress report correctly indicates that implementation of poverty reduction programs suffered setbacks owing to weak revenue performance and delays in external budget support since late 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet